STUDY OF A NEW TECHNOLOGICAL EQUIPMENT FOR CLEANING COTTON RAW MATERIALS FROM GROSS POLLUTION - KULMATOV, ILHOM (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article presents an analysis of the scientific work carried out to improve the technology of cleaning cotton from large impurities, and also describes the results of the experimental work of the proposed technological equipment. It is expected that the effectiveness of cleaning from small impurities with a piled drum will increase as a result of the improvement of the recommended cotton cleaner from large impurities. as a result of not using a regeneration saw drum, the height of the cleaner and the efficient use of metal and energy consumption are achieved.